2011
DOI: 10.1002/dvg.20768
|View full text |Cite
|
Sign up to set email alerts
|

Indian hedgehog positively regulates calvarial ossification and modulates bone morphogenetic protein signaling

Abstract: Summary: Much is known regarding the role of Indian hedgehog (Ihh) in endochondral ossification, where Ihh regulates multiple steps of chondrocyte differentiation. The Ihh 2/2 phenotype is most notable for severely foreshortened limbs and a complete absence of mature osteoblasts. A far less explored phenotype in the Ihh 2/2 mutant is found in the calvaria, where bones form predominately through intramembranous ossification. We investigated the role of Ihh in calvarial bone ossification, finding that proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 52 publications
(56 reference statements)
6
103
0
Order By: Relevance
“…In one study, Ihh gain-and loss-offunction experiments in chick and mouse suggest that Hh signaling blocks the transition of pre-osteoblasts to osteoblasts (Abzhanov et al, 2007). An opposing study reported an overall decrease in markers of osteoblast differentiation in the calvaria of Ihh-null mice, suggesting that Hh signaling is pro-osteogenic (Lenton et al, 2011). As we did not detect any changes in osteoblast stage markers in ihha mutants, our data more closely fit the proosteogenic model put forth by Lenton et al, as their observed reduction in osteoblast markers might reflect differences in the rate of progenitor proliferation.…”
Section: Research Articlesupporting
confidence: 87%
See 2 more Smart Citations
“…In one study, Ihh gain-and loss-offunction experiments in chick and mouse suggest that Hh signaling blocks the transition of pre-osteoblasts to osteoblasts (Abzhanov et al, 2007). An opposing study reported an overall decrease in markers of osteoblast differentiation in the calvaria of Ihh-null mice, suggesting that Hh signaling is pro-osteogenic (Lenton et al, 2011). As we did not detect any changes in osteoblast stage markers in ihha mutants, our data more closely fit the proosteogenic model put forth by Lenton et al, as their observed reduction in osteoblast markers might reflect differences in the rate of progenitor proliferation.…”
Section: Research Articlesupporting
confidence: 87%
“…Development of the bone lineage involves the sequential transition of cells through discrete stages (Bruder and Caplan, 1989;Bruder and Caplan, 1990;Li et al, 2009), and Ihh function has previously been associated with regulating osteoblast differentiation during dermal bone development (Abzhanov et al, 2007;Lenton et al, 2011). As a change to this ordered progression could result in the observed phenotypes, we looked at bone lineage markers at 3 dpf and 5 dpf.…”
Section: Ordered Progression Through Stages Of Osteoblast Differentiamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the recent identification of genetic lesions in RAB23 and IHH in humans has implicated the involvement of Hh signaling in craniosynostosis pathophysiology (Jenkins et al, 2007;Klopocki et al, 2011). Although correlative studies in mouse have suggested a functional role for Ihh at late stages of suture development (Lenton et al, 2011), our lineage-tracing strategies provide the opportunity for investigating whether Hh responsiveness in primordial sutural and osteogenic precursors is crucial for even earlier processes pertaining to cell migration, specification and patterning (E7.5-8.5).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ihha is robustly expressed in blastemal Obs during regeneration (Avaron et al, 2006). Therefore, Ihha rather than Shha could account for ptch2 induction in regenerating Obs and in the direct control of osteoblast growth and/or differentiation in a manner recapitulating the proposed developmental roles of Ihh (Abzhanov et al, 2007;Huycke et al, 2012;Lenton et al, 2011;Long, 2012).…”
Section: Introductionmentioning
confidence: 98%